Classification of construction hazards for a universal hazard identification methodology - Mihić, Matej (Journal of Civil Engineering and Management, 2020)
Hazard identification in the construction industry is subject to a larger number of variables and unknowns than in other manufacturing industries making the hazard identification process more difficult and resulting in many injuries and fatalities. Moreover, previous research identified a research gap with regards to a universal hazard identification method. The results presented in this paper are a prerequisite for the development of such a method. Specifically, this paper proposes a novel classification of hazards in order to enable a more accurate hazard identification process which can take all possible hazards into consideration. Based on the theoretical framework, three hazard types are proposed in the research: self-induced hazards, peer-induced hazards, and global hazards. This classification is based on who is the source (who causes) the hazards in relation to who is affected by the hazards. Such classification was not identified in previous literature. This research also has practical implications. Such classification of hazards may influence safety experts to more actively focus on peer-induced hazards which are the hardest to identify. Finally, the outputs of the entire research should enable a more accurate and comprehensive hazard identification resulting in reduced injury and fatality rates in the construction industry.